Adverse Event Triggered Event Reporting for Devices: Report of a Food and Drug Administration–Supported Feasibility Pilot of Automated Adverse Event Reporting. Issue 2 (April 2016) - Reed, Terrie L.; Levy, Daniel; Steen, Leslie Tompkins; Roach, James; Taylor, Thomas; Call, Karen; Marion, Jill; Drozda, Joseph P.
Abstract : Despite US Food and Drug Administration (FDA) requirements for reporting medical device adverse events (AEs), only an estimated 10% of events are actually reported, and many of those lack important data. As part of its plan to strengthen postmarket surveillance of medical devices, the FDA sponsored a pilot project of the Adverse Event Triggered Event Reporting for Devices (ASTER-D) system developed by Outcome Sciences for automated AE reporting. The objective of this study is to test the feasibility of using ASTER-D to report medical device AEs. This was a cooperative effort of Outcome Sciences, FDA, and Mercy Health. The ASTER-D system enables a new functionality within the electronic health record for initiating AE reports from triggering events with prepopulated patient- and incident-specific data and minimal disruption to clinician workflow. The ASTER-D system employs health information exchange principles to automate medical device safety reporting and create a "safety information exchange" that allows safety information collected by various organizations to be available to others to facilitate postmarket surveillance. Mercy implemented ASTER-D for AEs related to coronary stents occurring in its cardiac catheterization laboratories in the context of Mercy's automated incident reporting software system and incorporated prototype unique device identifiers to link reports to key device attributes. Mercy succeeded in submitting an AE using ASTER-D to the FDA's Medical Product Safety Network database. This pilot provides proof of concept of ASTER-D's functionality. Further testing with greater numbers of AEs, with different devices, and in other healthcare settings, is required.